Recent advances in carbon based nanomaterials as electrochemical sensor for toxic metal ions in environmental applications. (2021) - Lochab, Amit; Sharma, Raksha; Kumar, Siddharth; Saxena, Reena
Abstract: Toxic metal ions are environmental pollutants that are non-biodegradable and hazardous for which World Health Organization has set a maximum permissible limit for safe drinking water. Various spectroscopic techniques are already in practice to monitor these toxic metals but electrochemical sensors have caught our attention because of their portability, low-cost and fast response. The sensitivity of these electrochemical sensors can be further improved by modifying with carbon based nanomaterials (CBNMs) because of their high conductivity, surface area and broad working potential. The review provides recent advances in the use of electrochemical sensors fabricated with CBNMs for detection of toxic metal ions.